Bone morphogenetic protein 13 in hepatic stellate cells and hepatic fibrosis. Issue 10 (20th April 2022) - Peschl, Vanessa; Seitz, Tatjana; Sommer, Judith; Thasler, Wolfgang; Bosserhoff, Anja; Hellerbrand, Claus
Abstract: Hepatic fibrosis can be considered as a deregulated wound healing process in response to chronic liver injury. Bone morphogenetic protein 13 (BMP13) has been described to promote bone and tendon repair. In this study, we aimed to analyze the expression and function of BMP13 in hepatic fibrosis. We found increased BMP13 expression during the activation of hepatic stellate cells (HSCs), which is known as the key event of hepatic fibrosis. Fitting to this, BMP13 was elevated in murine models of hepatic fibrosis, and immunofluorescence staining showed colocalization of BMP13 and α‐smooth muscle actin (α‐SMA), a marker for activated HSC, in cirrhotic human liver tissue. BMP13 depletion in activated human HSC reduced the phosphorylation of smad1/5/9 and the expression of the transcription factor inhibitor of differentiation 1 (ID1), a known BMP target gene and profibrogenic factor. Furthermore, BMP13‐depletion led to reduced proliferation and downregulation of collagen I α1 (COL1A1) and α‐SMA, and, interestingly, also reduced phosphorylation of extracellular signal‐regulated kinases (ERK). Conversely, stimulation with recombinant BMP13 induced the phosphorylation of smad1/5/9 and ERK, as well as the proliferation and the expression of ID1, COL1A1,  and α‐SMA in HSCs. These stimulatory effects were inhibited by dorsomorphin 1, a small‐molecule inhibitor of the BMP‐type I receptors activin receptor‐like kinase‐2 and ‐3, which are both expressed by HSC. In summary, these data indicate increased BMP13 expression in hepatic fibrosis as a profibrogenic factor. Thus, this soluble growth factor might have the potential as a new fibrosis marker and antifibrogenic therapeutic target in patients with chronic liver disease.